2016
DOI: 10.1017/s0954102016000274
|View full text |Cite
|
Sign up to set email alerts
|

Depositional history of sedimentary sterols around Penguin Island, Antarctica

Abstract: Lipid biomarkers are potential tools for identifying the sources, diagenesis and reactivity of organic matter (OM) in marine systems, including in Antarctica where the particular environmental characteristics have motivated several studies of organic markers. Sedimentary sterol distributions were determined in two sediment cores (PGI-1 and PGI-2) collected from the marine environment around Penguin Island, Antarctica, during the 2007–08 summer. The cores were sectioned at 1 cm intervals and the sterols were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Similarly, the 5αstanol/Δ 5 -sterol ratios are found higher in surface sediments with comparatively lower bottom water DO levels in the Yangtze River estuary (Zhu et al, 2012) and the PRE (Guo, 2015), implying that the ratio records in downcore sediments may reflect bottom water (surface sediment) redox conditions in the past. This is followed by a recent study on short cores around Penguin Island, demonstrating that sedimentary variations of the 5α-stanol/Δ 5sterol ratios may be attributed to changes in bottom water conditions at the study sites at the time of deposition (Ceschim et al, 2016). Accordingly, in this study, sedimentary C 28 Δ 22 /Δ 5,22 ratios are likely also predominantly determined by bottom water DO conditions that modulate the extent of anaerobic conversion of C 28 Δ 5,22 at its initial deposition as a component of surface sediments.…”
Section: Origin Of Stanolsmentioning
confidence: 77%
“…Similarly, the 5αstanol/Δ 5 -sterol ratios are found higher in surface sediments with comparatively lower bottom water DO levels in the Yangtze River estuary (Zhu et al, 2012) and the PRE (Guo, 2015), implying that the ratio records in downcore sediments may reflect bottom water (surface sediment) redox conditions in the past. This is followed by a recent study on short cores around Penguin Island, demonstrating that sedimentary variations of the 5α-stanol/Δ 5sterol ratios may be attributed to changes in bottom water conditions at the study sites at the time of deposition (Ceschim et al, 2016). Accordingly, in this study, sedimentary C 28 Δ 22 /Δ 5,22 ratios are likely also predominantly determined by bottom water DO conditions that modulate the extent of anaerobic conversion of C 28 Δ 5,22 at its initial deposition as a component of surface sediments.…”
Section: Origin Of Stanolsmentioning
confidence: 77%
“…Multi-proxy paleolimnological approaches that include independent tracers add confidence to historical records. Lipid biomarkers have shown potential for tracking seabird and human enrichment to lake/pond sediments (Ceschim et al, 2016).. In addition, previous research showed that pond sediments adjacent to bird colonies were greatly enriched in cholesterol relative to the plant-derived sitosterol (Cheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%